From Sponge City to Sponge Earth - Zhu, Yuanyou; Zhang, Linus ; 0000-0003-2676-3420 (Lecture Notes in Civil Engineering, 2025)
Water is most important to all lives on this planet, but there is a lot of fresh water wasted on the land. With the rapid increase of population, the humankind shall pay more attention to water storage on the land. Inspired by the “sponge city” theory put forward by some researchers in urban construction in recent years, the authors try to put forward the “sponge earth” theory, so as to make enough use of the freshwater resources on land and explore more inhabitable spaces for humankind. Although the sponge earth also includes water inﬁltration, stagnation, storage, puriﬁcation, utilization and discharge, in a general and much broader view, this article focuses more on water inﬁltration, stagnation and storage.